Assessment of Preparedness of Dental Graduates and Postgraduates in the Management of Medical Emergencies - Qurat Ul Ain, Saad Haroon, Zainab Qasim Butt, Saqlain Bin Syed Gilani, Sufyan Ahmed, Danish Bin Sattar (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: This study aimed to assess the type of training concerning the management of medical emergencies, received by house officers and postgraduate trainees in different dental teaching institutes of Rawalpindi and Islamabad, Pakistan. Materials and Methods: A questionnaire was distributed in different dental teaching hospitals in Rawalpindi and Islamabad. It contained questions regarding what type of training they received, and whether they perceived that the training was sufficient when it was needed during a medical emergency. Data was analyzed by SPSS and frequencies were recorded. Results: All participants had received either theoretical or practical training. Less than 20% of house officers and postgraduate trainees perceived that they have handled a medical emergency ‘well’. Conclusion: This shows that our current curriculum is focused on the ‘theory’ and lacks practical training which leads to underprepared practitioners. To improve their skills, students should undergo drills and artificial and simulation-based training. Keywords: Medical emergency, CPR, BLS, dental practice